CYP2C19-rs4986893 confers risk to major depressive disorder and bipolar disorder in the Han Chinese population whereas ABCB1-rs1045642 acts as a protective factor - Ting Zhang; Qingmin Rao; Kangguang Lin; Yongyin He; Jintai Cai; Mengxin Yang; Ying Xu; Le Hou; Yulong Lin; Haiying Liu (BMC Psychiatry, 2023)
Abstract Background Genetic risks may predispose individuals to major mood disorders differently. This study investigated the gene polymorphisms of previously reported candidate genes for major depressive disorder (MDD) and bipolar disorder (BPD) in the Han Chinese population. Methods Twenty loci of 13 candidate genes were detected by MALDI-TOF mass spectrometry in 439 patients with MDD, 600 patients with BPD, and 464 healthy controls. The distribution of genotypes in alleles, Hardy-Weinberg equilibrium, and genetic association were analyzed using the PLINK software. The linkage of disequilibrium and haplotype analyses were performed using the Haploview software. Results Out of the 20 loci analyzed, CYP2C19-rs4986893, ABCB1-rs1045642, and SCN2A-rs17183814 passed Bonferroni correction; their statistical powers were > 55%. The minor allele frequencies (MAF) of CYP2C19-rs4986893 in the MDD group (0.0547) and BPD group (0.0533) were higher than that of the control group (0.0259, P < 0.05), leading to the odds ratios (ORs) of MDD (2.178) and BPD (2.122), respectively. In contrast, the lower MAFs of ABCB1-rs1045642 were observed in both MDD (0.3599, OR = 0.726) and BPD (0.3700, OR = 0.758) groups than controls (0.4364, P < 0.05). The MDD group had a higher MAF of SCN2A-rs17183814 than controls (0.1743 vs. 0.1207, OR = 1.538, P < 0.05). Moreover, a G-A haplotype composed by CYP2C19-rs4986893 and -rs4244285 was associated with BPD (OR = 1.361, P < 0.01), and the A-G haplotype increased the risks to both MDD (OR = 2.306, P < 0.01) and BPD (OR = 2.332, P < 0.001). The CYP2C19 intermediate metabolizer and poor metabolizer (IM&PM) status was related to the raised risk of both MDD (OR = 1.547, P < 0.01) and BPD (OR = 1.808, P < 0.001). Conclusion Our data indicate that the impaired CYP2C19 metabolism caused by the haplotypes integrated by CYP2C19 alleles might confer the risk to MDD and BPD, whereas the ABCB1-rs1045642 T allele serves as a protective factor.